Atypical transport for GdTe1.8 upon substitution with Se: Strong electron-phonon coupling in polaronic conduction. (15th March 2021) - Poddig, Hagen; Hobbis, Dean; Doert, Thomas; Nolas, George S.
Abstract: The chemistry of new materials and the effects of chemical substitutions on physical properties continues to be of intense interest as it directly affects many technological fields. The synthesis and temperature dependent transport properties of GdTe1.62 Se0.18 were investigated revealing polaronic transport upon simple alloying with selenium. Temperature-dependent resistivity and thermopower measurements indicate strong electron-phonon coupling, as compared to the few other chalcogenides that display such transport. In addition, the low thermal conductivity is intrinsic for this material, and a result of the stacking arrangement in the crystal structure as well as of a statistical disordered Te2 2– anion. Graphical abstract: Image, graphical abstract